1994
DOI: 10.1021/bi00199a017
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Phenylalanine 34 of Human Dihydrofolate Reductase in Substrate and Inhibitor Binding and in Catalysis

Abstract: Directed mutagenesis has been used to construct five variants of human dihydrofolate reductase in which smaller residues are substituted for phenylalanine 34, a residue participating in the binding of substrate and methotrexate by interaction with their pteridine rings. The variant enzymes are stable and have decreased affinities for methotrexate (by factors of 2700-60000 at pH 7.65) due to a decreased rate of methotrexate association and a much larger increase in the rate constant for dissociation. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 17 publications
1
32
0
Order By: Relevance
“…MTX has been shown to stabilize DHFR in vitro and, in particular, in ternary complex when DHFR is bound to NADPH/NADP (Nakano et al, 1994); however, it has not been previously shown in a cellular context. Demonstration of stabilization of DHFR by MTX in cells has been difficult because DHFR is always bound to NADPH.…”
Section: Protection Of Dhfr By Mtx From Degradation After Nadps Treatmentioning
confidence: 87%
“…MTX has been shown to stabilize DHFR in vitro and, in particular, in ternary complex when DHFR is bound to NADPH/NADP (Nakano et al, 1994); however, it has not been previously shown in a cellular context. Demonstration of stabilization of DHFR by MTX in cells has been difficult because DHFR is always bound to NADPH.…”
Section: Protection Of Dhfr By Mtx From Degradation After Nadps Treatmentioning
confidence: 87%
“…Phe-34 3 Ser does not allow reconstitution of activity. This may be a result of its lower solubility, or of the 5,000-fold reduction in catalytic efficiency relative to the wild-type (22). This position is conserved in 35 of 37 natural sequences (HSSP database file:1drf.hssp) (27) and is part of a hydrophobic cluster in F [1,2]; it may be necessary for the proper folding or stability of this fragment.…”
Section: Discussionmentioning
confidence: 99%
“…S5) as has been previously reported (20,21). The data were found to be well described by the equation for substrate inhibition detailed by Nakano et al (22). Although this equation yields V max /K m , it does not provide values for these parameters separately.…”
mentioning
confidence: 89%